A Case Study Exploring Side-Channel Attacks On Pet Wearables - Levina, Alla; Varyukhin, Vladimir; Kaplun, Dmitry; Zamansky, Anna; van der Linden, Dirk (IAENG international journal of computer science, 2021)
IoT has long since come to the pet industry resulting in a proliferation of data-intensive devices including tracking anything from activity, health, to location. The resulting 'Internet of Pets' is generating large volumes of animal data which, due to the close link between the digital profile of companion animals held as pets (e.g., cats and dogs) and their caregivers holds significant security and privacy implications. In this case study we explore the vulnerability of such pet wearables to side-channel attacks, describing our implementation of an electromagnetic attack on a now discontinued dog activity tracker. We show how we were able to successfully exfiltrate data from the device during the Base64 encoding process and discuss what implications this holds for the security of these devices, given the lack of protection that animal data is afforded under extant existing data protection policy and legislation.